Non-selective beta-blockers and the incidence of hepatocellular carcinoma in patients with cirrhosis: a meta-analysis - He, Xinyi; Zhao, Zimo; Jiang, Xi; Sun, Yan (Frontiers in Pharmacology, 2023)
Background: Hepatocellular carcinoma (HCC) is a serious complication of cirrhosis. Currently, non-selective beta-blockers (NSBB) is commonly used to treat portal hypertension in patients with cirrhosis. The latest research shows that NSBB can induce apoptosis and S phase arrest in liver cancer cells and inhibit the development of hepatic vascular endothelial cells, which may be effective in preventing HCC in cirrhosis patients. Aims: To determine the relationship between different NSBB and HCC incidence in patients with cirrhosis. Methods: We searched the Cochrane database, MEDLINE, EMBASE, PubMed, and Web of Science.Cohort studies, case-control studies and randomized controlled trials (RCTs) were included if they involved cirrhosis patients who were divided into an experimental group using NSBB and a control group with any interventions. Based on heterogeneity, we calculated odds ratio (OR) and 95% confidence interval (CI) using random-effect models. We also conducted subgroup analysis to explore the source of heterogeneity. Sensitivity analysis and publication bias detection were performed.Results: 47 studies including 38 reported HCC incidence, 26 reported HCC-related mortality and 39 reported overall mortality. The HCC incidence between the experimental group and the control group was OR=0.87 (0.69,1.10), P=0.000, I 2 =81.8%. There were no significant association between propranolol (OR=0.94, 95%CI 0.62-1.44) or timolol (OR=1.32, 95%CI 0.44-3.95) and HCC incidence, while the risk of HCC decreases by 26% and 38% with nadolol (OR=0.74, 95%CI 0.64-0.86) and carvedilol (OR=0.62, 95%CI 0.52-0.74) respectively.Different types of NSBB have different effects on the incidence of patients with cirrhosis of the liver, where nadolol and carvedilol can reduce the risk. And the effect of NSBB may vary in ethnicity. Propranolol can reduce HCC incidence in Europe and America.